Uso de tecnologias digitais para aprender português língua não materna: Estratégias de confirmação de resultados e de construção de conhecimento (Revista Lusófona de Educação, 2026)
The Use of Digital Technologies in Learning Portuguese as a Non-Native Language: Strategies for the Validation of Results and the Construction of KnowledgeAbstract: This study, which is part of a broader research project on the use of digital technologies (DT) to learn and teach Portuguese as a non-native language (PNNL), presents and discusses the results regarding the degree of confidence that learners and teachers place in digital media in this context, as well as the strategies they use to confirm the outputs of the DT, as to build knowledge in Portuguese. The study also addresses the guidance learners are provided by teachers to in order to use DT appropriately. A qualitative methodological approach was used in this case study. 34 semi-structured interviews were carried out (with 24 students and 10 teachers from Portuguese courses at a higher education institution). Results show that the majority of learners show confidence in DT, even if in varying degrees, and the practice of confirming the outputs obtained through different strategies, among which the use of more than one DT for the same purpose. Learners also point to the lack of guidance provided by PNNL teachers in the use of DTs, a perception confirmed by the teachers themselves, who nevertheless consider, paradoxically, that learners’ trust in DTs is excessive. The results suggest that DT should be incorporated into teaching practices, a need that has now been exacerbated by the current proliferation of Generative Artificial Intelligence tools.Keywords: Digital Technologies; Portuguese as a Non-native Language; Confirmation Strategies; Knowledge Building; Non-native learners.